Combination of inflammatory and vascular markers in the febrile phase of dengue is associated with more severe outcomes - Yacoub, S (University of Oxford, 2021)
Biomarkers from patients with dengue in the first 3 days of illness from Vietnam, Cambodia, Malaysia and El Salvador.